APLIKASI GOOGLE CLASSROOM SEBAGAI SOLUSI PEMBELAJARAN BAHASA INDONESIA SECARA DARING - Nur Indah Tri Ramadhani; Laili Etika Rahmawati (Linguistik : Jurnal Bahasa dan Sastra, 2021)
The purpose of this study is to describe the google classroom application as a solution for learning Indonesian in a bold way. This type of research is qualitative with a case study type. The data technique was carried out by interview and observation techniques. The object of this research is the students and teachers at SMP 2 Gatak class 7 who use the google classroom application in Indonesian language learning. The data analysis technique used was the interactive model of Miles and Huberman. The results showed that Google Classroom learning media is very necessary to be applied in learning activities in Indonesia at SMPN 2 Gatak, because it is in accordance with the learning conditions that are happening today, namely bold learning. The use of Google Classroom at SMPN 2 Gatak is the second most used media after Whatsapps by teachers.